Land planarian assemblages in protected areas of the interior atlantic forest: implications for conservation - Negrete, Lisandro Héctor Luis (2014)
Land planarians are an interesting group of free-living flatworms that can be useful as bioindicators because of their high sensitivity to environmental changes and low dispersal capacity. In this study, we describe and compare assemblages of land planarians from areas with different conservation degrees of the Interior Atlantic Forest (Misiones, Argentina), and assess factors that could be related to their abundance and richness. Eight sites were tracked in search of land planarians in Reserva de Vida Silvestre Urugua-í (RVSU) and Campo Anexo Manuel Belgrano (CAMB). Diurnal and nocturnal surveys were performed in each site along nine sampling campaigns. We collected 237 individuals belonging to 18 species of the subfamily Geoplaninae. All sites were dominated by Geoplana sp. 1 and Pasipha hauseri. The richness estimators showed that there would be more species in RVSU than in CAMB. The abundance and richness of land planarians was high during the night and after rainfalls, suggesting an increased activity of flatworms under such conditions. The abundance and richness of land planarians were also related to the conservation condition of the sites. Disturbed sites showed less abundance and richness, and were segregated from non-disturbed ones by nmMDS analysis. Beta diversity between sites was higher than expected, indicating that the species turnover between sites contributed more to the total richness (gamma diversity) than the alpha diversity.